Analisis Akuntansi Biaya Digital Marketing terhadap Customer Acquisition Cost dan Dampaknya pada Laba Bersih Perusahaan E-Commerce di Wilayah Surakarta - Nurita Elfani Prasetyaningrum prasetyaningrum; Ramadhian Agus Triono Sudalyo (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2026)
This study aims to analyze the accounting treatment of digital marketing costs on Customer Acquisition Cost (CAC) and its impact on the net profit of e-commerce companies in the Surakarta region. The Surakarta region covers Surakarta City, Boyolali Regency, Sragen Regency, Karanganyar Regency, Wonogiri Regency, Klaten Regency, and Sukoharjo Regency. The research uses a quantitative approach with a purposive sampling technique, involving 100 e-commerce companies as the research sample. Data were collected through questionnaires and financial documentation. The variables consist of digital marketing cost accounting, Customer Acquisition Cost, and net profit. Data analysis employed multiple linear regression with classical assumption tests. The results revealed that digital marketing cost accounting has a significant negative effect on CAC (β=−0.452, p<0.05), CAC has a significant negative effect on net profit (β=−0.488, p<0.05), and CAC partially mediates the effect of digital marketing cost accounting on net profit. This research contributes to the development of management accounting practices in the digital era, particularly for e-commerce businesses in the Surakarta region.